2007
DOI: 10.1155/2007/59786
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Disturbances in Voltage Signals for Power Quality Analysis Using HOS

Abstract: This paper outlines a higher-order statistics (HOS)-based technique for detecting abnormal conditions in voltage signals. The main advantage introduced by the proposed technique refers to its capability to detect voltage disturbances and their start and end points in a frame whose length corresponds to, at least, N = 16 samples or 1/16 of the fundamental component if a sampling rate equal to f s = 256 × 60 Hz is considered. This feature allows the detection of disturbances in submultiples or multiples of one-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 24 publications
0
22
0
7
Order By: Relevance
“…Within the transient detection context, the target PQ event is always considered non-Gaussian, while the floor is assumed to be stationary Gaussian signal [4,[22][23][24]. Thus, using HOS would help to locate the transient in a qualitative way, with a rough approximation.…”
Section: Higher-order Statistics and The Spectral Kurtosismentioning
confidence: 99%
“…Within the transient detection context, the target PQ event is always considered non-Gaussian, while the floor is assumed to be stationary Gaussian signal [4,[22][23][24]. Thus, using HOS would help to locate the transient in a qualitative way, with a rough approximation.…”
Section: Higher-order Statistics and The Spectral Kurtosismentioning
confidence: 99%
“…During the last decade, some researches [7,15,24] have demonstrated the usage of HOS features for PQ monitoring. The motivation of HOS in PQ analysis is twofold.…”
Section: Higher-order Statistics For Pq Monitoring: An Enhancement Prmentioning
confidence: 99%
“…In the same direction, Gu and Bollen [6] found relevant characteristics associated to PQ events in the time and frequency domains. The work by Ribeiro et al is also remarkable [7], which extracted new time-domain features based in cumulants. The same authors performed the classification of single and multiple disturbances using HOS in the time domain and Bayes' theory-based techniques [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, noise degrades the effectiveness of these second-order techniques. Recent studies concluded that a better characterization of symmetry and shape of the waveform are possible via the 3erd and 4th higher-order statistics (HOS), that also account for the nonlinear assessment of the signals [9], [10].…”
Section: Introductionmentioning
confidence: 99%